2014
DOI: 10.1002/2013ja019466
|View full text |Cite
|
Sign up to set email alerts
|

A study on ionospheric scintillation near the EIA crest in relation to equatorial electrodynamics

Abstract: Equatorial electrojet (EEJ) data, which are considered as a proxy index of equatorial electric field, are analyzed in conjunction with equatorial ionosonde, total electron content (TEC) and scintillation data near the equatorial ionization anomaly (EIA) crest for the equinoctial months of high solar activity years (2011)(2012) to identify any precursor index of postsunset evolution of equatorial electron density irregularities and subsequent occurrence of scintillation near the northern EIA crest. Only geomagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The H component observed at the station CMRN on these days (not shown here) exhibits an afternoon secondary maximum, which is the precursor of scintillation following Chatterjee et al (2014), and scintillations are observed. Ngwira et al, 2013, studied scintillations in 4 African GPS stations from West to East Africa.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The H component observed at the station CMRN on these days (not shown here) exhibits an afternoon secondary maximum, which is the precursor of scintillation following Chatterjee et al (2014), and scintillations are observed. Ngwira et al, 2013, studied scintillations in 4 African GPS stations from West to East Africa.…”
Section: Discussionmentioning
confidence: 72%
“…Depending on the scale size irregularities, different observations are made, "the meter scale size irregularities producing plumes in the VHF backscatter radar maps, the decameter sizes that give rise to the spread F echoes in the ionograms, and the hectometer to kilometer sizes produce VHF and UHF radio wave scintillation (Abdu et al, 1983)". Recently, Chatterjee and Chakraborty (2013) and Chatterjee et al (2014) studied the scintillations near the crest of the EIA in India, during quiet magnetic days; in their work, they connected EIA, EEJ and scintillations. They found that a post sunset enhancement of the TEC and afternoon enhancement in EEJ are good precursors for postsunset occurrence of scintillation.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure of this combined system is complex to explain for estimating TEC data that is not an issue in this study. A number of relevant studies exist (Edwards, 1989;Lin et al, 2001;Liu et al, 2004;Tsai and Tsai, 2004;Nishihashi et al, 2009;Pulinets and Boyarchuk, 2005;Liu et al, 2006;Klimenko et al, 2012;Lin, 2013;Chuo, 2014, Hayakawa, 2016Chatterjee et al, 2014;Nenovski et al, 2015;Thomas et al, 2017;Wang et al, 2017). TEC maps for three time periods are used in this study.…”
Section: Data Sourcementioning
confidence: 99%
“…This finding is consistent with the diurnal occurrence of scintillation observed in all seasons, which suggests that is associated with the presence of E sb . Furthermore, it is possible that the scintillation events observed in the late afternoon sector could be due to plasma irregularities in the F-region (e.g., Chatterjee et al 2014); however, post sunset F-region scintillations are normally observed after~19:00 LT (Somayajulu et al 1984;Gwal et al 2004;Carter et al 2013;Narayanan et al 2014). Therefore, it is unlikely that the late-afternoon GPS scintillation events analyzed here (~17:00 LT) are due to F-region plasma irregularities.…”
Section: Characteristics Of Daytime Ghz Scintillation In the Vicinitymentioning
confidence: 99%